ANALISIS RENDAHNYA KEMAMPUAN LITERASI MEMBACA SISWA SERTA UPAYA PENINGKATANNYA MELALUI FLIPBOOK DIGITAL - Muhammad Sholihul Huda; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study analyzes the low ability of fourth-grade students at SD Negeri Soropadan to understand important information and general messages in reading texts within the framework of the School Literacy Movement . The problem emerged from diagnostic tests showing an average comprehension score of only 61.99%, indicating limited reading understanding despite routine literacy activities. The research aims to describe students’ reading-comprehension level, identify contributing factors to the low performance, and propose an alternative solution through digital flipbook media. This study employed a qualitative descriptive approach, supported by test results, teacher interviews, and documentation. Data were validated using triangulation of sources and techniques, and analyzed through reduction, display, and conclusion drawing. The results revealed that students tended to read mechanically without grasping textual meaning, mainly due to monotonous reading materials and low learning motivation. Literature analysis from five related studies confirmed that digital flipbooks effectively enhance learning outcomes, motivation, and comprehension through interactive multimedia elements combining text, images, videos, and quizzes. Consequently, the use of digital flipbooks is recommended as an innovative medium to strengthen the implementation of the School Literacy Movement, increase student engagement, and improve their ability to identify key information and main messages in reading texts. Keywords: School Literacy Movement, reading comprehension, digital flipbook, elementary education, motivation ABSTRAK Penelitian ini bertujuan untuk menganalisis rendahnya kemampuan siswa kelas IV SD Negeri Soropadan dalam memahami informasi penting dan pesan umum pada teks bacaan dalam konteks Gerakan Literasi Sekolah (GLS). Permasalahan ini muncul berdasarkan hasil tes diagnostik yang menunjukkan rata-rata nilai pemahaman hanya 61,99%, menandakan rendahnya kemampuan membaca pemahaman meskipun kegiatan literasi rutin telah dilakukan. Penelitian ini bertujuan mendeskripsikan tingkat kemampuan siswa, mengidentifikasi faktor penyebab rendahnya hasil belajar, serta menawarkan solusi alternatif melalui penggunaan media flipbook digital. Pendekatan yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data berupa tes, wawancara guru, dan dokumentasi. Data divalidasi menggunakan triangulasi sumber dan teknik, kemudian dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa cenderung membaca tanpa memahami isi bacaan, disebabkan oleh kurangnya variasi media dan rendahnya motivasi belajar. Kajian dari lima penelitian relevan mendukung bahwa media flipbook digital efektif meningkatkan hasil belajar, motivasi, dan pemahaman melalui fitur interaktif berupa teks, gambar, video, dan kuis. Oleh karena itu, media flipbook digital direkomendasikan sebagai solusi inovatif untuk memperkuat pelaksanaan GLS dan meningkatkan kemampuan siswa dalam memahami isi bacaan secara bermakna. Kata Kunci: Gerakan Literasi Sekolah, membaca pemahaman, flipbook digital, sekolah dasar, motivasi